2015
DOI: 10.1186/s13063-015-0656-7
|View full text |Cite
|
Sign up to set email alerts
|

The POSE study - panic control treatment versus panic-focused psychodynamic psychotherapy under randomized and self-selection conditions: study protocol for a randomized controlled trial

Abstract: BackgroundPanic disorder with or without agoraphobia is a commonly occurring disorder affecting 2 to 3% of the population in Sweden. Untreated, panic disorder is a chronic condition that significantly increases the risk for psychiatric comorbidity, morbidity and mortality, employment difficulties, and healthcare utilization. Cognitive behavioral approaches are the recommended first-line treatment for panic disorder; however, many patients in routine care receive another evidence-based psychotherapy, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Participants in the WL condition were re-randomized to either the Random or Choice conditions after twelve weeks. Details of the trial protocol are available in Sandell et al (2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in the WL condition were re-randomized to either the Random or Choice conditions after twelve weeks. Details of the trial protocol are available in Sandell et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…The present study uses data from the first doubly randomized controlled preference trial (DRCPT) (Sandell et al, 2015) examining whether outcomes for PD/A are superior when patients choose their treatment compared to when the treatment is randomly allocated. The two forms of psychotherapy offered to the participants were a form of CBT called Panic Control Treatment (PCT; Craske & Barlow, 2006) and Panic Focused Psychodynamic Psychotherapy (PFPP;Milrod et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Treatments were delivered and data were collected between the years 2012 and 2018. A detailed presentation of the procedures in the study can be found in the published trial protocol [24].…”
Section: Methodsmentioning
confidence: 99%
“…Nordic translations and psychometric analyses of instruments used internationally are important and there are several notable examples of this effort [19][20][21][22][23]. The aim of this study was to evaluate the psychometric properties (including the factor structure) of the PDSS and PDSS-SR in a large, treatment-seeking sample of adults with a DSM-IV diagnosis of PD or PDA who were recruited to a randomized controlled preference trial of cognitive behavioral therapy and brief, panic-focused psychodynamic therapy (Project POSE [24]).…”
Section: Introductionmentioning
confidence: 99%
“… 4 There are, to our knowledge, few studies focused on a patient’s choice of psychotherapy. 5 , 6 Psychotherapy includes various types, including Internet psychotherapy; psychotherapy from artificial intelligence; personal development books focused on patient education; conventional forms of psychotherapy such as cognitive psychotherapy; and dynamic, interpersonal, or supportive therapy. 5 , 7 For example, Berle et al made a significant contribution to the issue of patient preferences for treatment or therapy delivered face-to-face or via the Internet.…”
Section: Introductionmentioning
confidence: 99%